Predictive value of calculated plasma osmolality and atherogenic index of plasma for chronic limb-threatening ischemia in lower extremity artery disease - Pala, Arda Aybars; Urcun, Yusuf Salim (The European Research Journal, 2021)
Objectives: Chronic limb-threatening ischemia (CLTI) is the end-stage form of lower extremity artery disease (LEAD) whose main reason is atherosclerosis. Plasma osmolality (PO) and plasma lipid levels affect the development and progression of atherosclerosis directly. The purpose of this study was to investigate the predictive effect of PO and atherogenic index of plasma (AIP) for the development of CLTI. Methods: A total of 324 patients who were diagnosed with LEAD were analyzed retrospectively. The clinical stage of the disease was evaluated according to the Rutherford classification, and patients without CLTI were defined as “Group 1” and patients with CLTI as “Group 2”. Results: There were 248 patients (mean age 64.44 ± 9.05 years and 73.4% male) in Group 1, and 76 patients (mean age 66.62 ± 8.22 years and 76.3% male) in Group 2. In the multivariate regression analysis, CAD, PO, CRP and AIP were defined as independent predictive factors for the development of CLTI (p = 0.015, p < 0.001, p = 0.007, p < 0.001; respectively). ROC curve analysis showed that, PO cut-off value for CLTI development was 293.28 mOsm/kg (AUC: 0.821, p < 0.001) with 75% sensitivity and 74.2% specificity, and AIP cut-off value was 0.23 (AUC: 0.740, p < 0.001) with 67.1% sensitivity and 68.5% specificity. Conclusions: The PO and AIP values in LEAD patients may be used as the new biomarkers of atherosclerosis progression, and therefore as predictive factors for the development of CLTI.